Comparison of Intraocular Pressure and Central Corneal Thickness Measurements of Obese, Overweight, and Healthy Volunteers - Saguş Aydın, Mehtap; Akyüz Ünsal, Ayşe İpek and Aydın Eroğlu, Sayime and Ünübol, Mustafa and Ünsal, Mustafa Gökhan and Kurt Ömürlü, İmran and Demirci, Buket (Cerrahpaşa Medical Journal, 2020)
Objective: To compare the central corneal thickness (CCT) and intraocular pressure (IOP) of obese, overweight, and healthy volunteers. Methods: This prospective case-control study included patients of endocrinology department and healthy volunteers on June-November 2017. Diabetes, hypertension, glaucoma, corneal surface diseases, corneal edema and patients under the age of 18 years were the exclusion criteria. Group 1 consisted of healthy volunteers (BMI: 18.5-24.9 kg/m2), Group 2 overweight (BMI: 25.0-29.9 kg/m2), and Group 3 obese(BMI >30 kg/m2). Anterior and posterior segment assessment, visual acuity, IOP with noncontact tonometer and CCT with optical coherence tomography were evaluated. Results: Three hundred and forty-four eyes of 172 patients were evaluated. A weak positive correlation between BMI and IOP (r=0.191, p<0.001) and significantly higher IOP in group 3 were detected (p=0.003). No statistical difference between Group 1 and Group 2 (Group 1/2/3: 15.8±3.2/16.1±3.3/17.6±4.5 mmHg). A positive correlation was found between the CCT and IOP (r=0.349, p<0.001). Conclusion: BMI did not effect the CCT. However, it seems that IOP tended to increase with an increase in BMI. Obesity could have an effect on IOP. Therefore, weight control could be important in patients who need IOP regulation. Further studies performing IOP and CCT measurements at the same time of the day are required. Cite this article as: Saguş Aydın M, Akyüz Ünsal Aİ, Aydın Eroğlu S, Ünübol M, Ünsal MG, Kurt Ömürlü İ, et al. Comparison of Intraocular Pressure and Central Corneal Thickness Measurements of Obese, Overweight, and Healthy Volunteers. Cerrahpaşa Medical Journal 2020; 44(2): 98-103.